Processing and mechanical properties of B4C reinforced Al matrix composites - GÜLLÜOĞLU, ARİF NİHAT; GÜLSOY, HAMİT ÖZKAN (ELSEVIER SCIENCE SA, 2009)
Aluminum matrix composites are emerging as advance engineering materials due to its high specific strength and stiffness, good wear resistance and high temperature properties. Properties of Al reinforced with Al2O3 and SiC are widely investigated. In the present study, mechanical properties of B4C reinforced Al matrix is investigated due to higher hardness and lower density properties than SiC and Al2O3. The high temperature deformation behavior of 5, 10, 15 and 20wt% B4C powder having an average particle diameter of about 10 mu m aluminum matrix composite sintered at 650 degrees C was investigated by creep tests at temperatures ranging from 400 to 450 degrees C and creep resistance of Al alloy is enhanced by the presence of B4C particles. Measurement of impact and hardness properties of composites showed that impact values decrease and hardness values increased with increase in weight fraction of reinforcement. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Metal matrix composite; Powder metallurgy; Sintering; Mechanical properties; POWDER-METALLURGY; WEAR BEHAVIOR; BORON-CARBIDE; ALUMINUM; MICROSTRUCTURE; FABRICATION